(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In clause the urgency offormation of culture of thinking of the teacher of a polyart structure is considered (examined), the variants of modular training are described on the basis of integration o f arts. The examples of control questions assessment of levels forming of culture of thinking of the student are offered.